Awe weakens the AIDS-related stigma: The mediation effects of connectedness and empathy - Luo, Li; Yang, Dong; Tian, Yu; Gao, Wei; Yang, Jiemin; Yuan, Jiajin (Frontiers in Psychiatry, 2022)
Stigma towards people with HIV or AIDS produces significant harms to their life and also hinders the prevention of AIDS. In the present study, we tested whether awe can weaken AIDS-related stigma and the mediating role of connectedness and empathy between them through a cross-sectional study (Study 1, N = 372) and two experimental studies (Study 2a and 2b, N = 110 and N = 180 respectively). Results showed that awe reduced AIDS-related stigma (Study 2a and 2b), via the serial mediation of connectedness and empathy (Study 1 and 2b). These findings suggest that the experience of awe increases one’s connectedness to the world, which then enhances empathy and decreases AIDS-related stigma. This study expands our understanding of the relationship between awe and stigma, providing empirical basis for decreasing social prejudice to others.